Teachers' Communication Patterns In The Learning Process With Children With Special Needs At The Fitria Bogor Special School - Sugih Gumilar, S.I.Kom; Dr. Ika Yuliasari, M.Si; Dr. Noviyanty Elizabeth Ayuna, M.Pd (International Journal of Technology and Education Research, 2025)
This study examines the communication patterns used by teachers in an inclusive classroom environment at SLB Fitria Bogor, an extraordinary school in Indonesia. Using a qualitative descriptive approach, this study explores how interpersonal communication is built between teachers and students with different types of disabilities, especially deaf students. Data were collected through in-depth interviews, non-participatory classroom observations, and document analysis.The results of the study showed that the teacher integrated sign language, facial expressions, body movements, lip reading, and visual media to build understanding and support the learning process. Despite facing various challenges such as limited vocabulary comprehension, differences in fluency in sign language, and lack of parental involvement, teachers demonstrate flexible communication patterns to overcome these barriers. This research contributes to the field of educational communication for children with special needs, as well as highlights the importance of using flexible communication techniques in the teaching environment for deaf and several other deaf children.